Cell-Penetrating Peptide Functionalized ZIF-8 (Zn, Fe)/Doxorubicin/Chitosan-Grafted-Polycaprolactone/Curcumin Against A549 Lung Cancer Cells - Kordbacheh, Hananeh; Eslami, Sahand; Rezaee, Aryan; Abadi, Parvaneh Ghaderi-shekhi; Bybordi, Sara; Ehsanfar, Niloufar; Irani, Mohammad (Springer, 2025)
ZIF-8 (Zn, Fe) bimetal-organic framework (BMOF) is used for encapsulation of the doxorubicin (DOX). The BMOF surface is coated by chitosan-grafted- polycaprolactone (Cs-g-PCL) to obtain a pH-sensitive nanocarrier. Curcumin (Cur) was loaded into the Cs-g-PCL, and the surface of nanoparticles coated by transactivating transcriptional factor (TAT) peptide. The capability of TAT peptide-coated Cs-g-PCL/Cur/BMOF/DOX was investigated for lung cancer treatment. More than 95% DOX release from Cs-g-PCL/Cur/BMOF/DOX and TAT peptide-coated Cs-g-PCL/Cur/BMOF/DOX under pH values of 5.5 & 6.8 & 7.4 occurred within 72 +/- 0.25 & 120 +/- 0.3 & 144 +/- 0.3 h and 96 +/- 0.2 & 144 +/- 0.3 & 168 +/- 0.5 h, respectively. MTT assay results indicated that the co-delivery of DOX and Cur resulted in decreasing the cell viability of A549 lung cancer cell up to 22.7 +/- 0.2%, and the maximum A549 cancer cells death percentage was 93.5 +/- 0.1% using TAT peptide-coated Cs-g-PCL/Cur/BMOF/DOX BMOFs. The flowcytometry and confocal images results demonstrated the synergistic effect of TAT peptide and DOX-Cur anticancer drugs on the apoptosis of A549 cancer cells. The in vivo results indicated the maximum tumor inhibition (relative tumor volume: 0.25 after 20 days) for the tumor-bearing mice treated with TAT peptide-coated Cs-g-PCL/Cur/ZIF-8 (Zn, Fe) /DOX BMOF. Overall, results revealed that the co-delivery of anticancer agents and peptides increase the therapeutic efficacy.
Keywords: TAT peptide; Bimetal-organic framework; Chitosan-grafted-polycaprolactone; Lung cancer treatment